Intratumorally delivered formulation, INT230-6, containing potent anticancer agents induces protective T cell immunity and memory. (3rd October 2019) - Bloom, Anja C.; Bender, Lewis H.; Tiwary, Shweta; Pasquet, Lise; Clark, Katharine; Jiang, Tianbo; Xia, Zheng; Morales-Kastresana, Aizea; Jones, Jennifer C.; Walters, Ian; Terabe, Masaki; Berzofsky, Jay A.
ABSTRACT: The benefits of anti-cancer agents extend beyond direct tumor killing. One aspect of cell death is the potential to release antigens that initiate adaptive immune responses. Here, a diffusion enhanced formulation, INT230-6, containing potent anti-cancer cytotoxic agents, was administered intratumorally into large (approx. 300mm 3 ) subcutaneous murine Colon26 tumors. Treatment resulted in regression from baseline in 100% of the tumors and complete response in up to 90%. CD8 + or CD8 + /CD4 + T cell double-depletion at treatment onset prevented complete responses, indicating a critical role of T cells in promoting complete tumor regression. Mice with complete response were protected from subcutaneous and intravenous re-challenge of Colon26 cells in a CD4 + /CD8 + dependent manner. Thus, immunological T cell memory was induced by INT230-6. Colon26 tumors express the endogenous retroviral protein gp70 containing the CD8 + T-cell AH-1 epitope. AH-1-specific CD8 + T cells were detected in peripheral blood of tumor-bearing mice and their frequency increased 14 days after treatment onset. AH-1-specific CD8 + T cells were also significantly enriched in tumors of untreated mice. These cells had an activated phenotype and highly expressed Programmed cell-death protein-1 (PD-1) but did not lead to tumor regression. CD8 + T cell tumor infiltrate also increased 11 days after treatment. INT230-6 synergized with checkpoint blockade, inducing a complete remission of the primary tumors and shrinking of untreated contralateral tumors, which demonstrates not only a local but also systemic immunological effect of the combined therapy. Similar T-cell dependent inhibition of tumor growth was also found in an orthotopic 4T1 breast cancer model.